Structural and ionic conduction study of enhanced bio-polymer electrolytes based carboxymethyl cellulose doped NH4Br - A. S., Samsudin (2017)
The increasing interest in green energy storage materials for electrochemical devices with the development of polymer as electrolytes candidate has attracted great attention recently. It can offer a number of high-value opportunities, provided that lower costs can be obtained besides environmental friendly. Due to this matter, this work presents the discovery on proton conducting bio-polymer electrolyte (BPE) by incorporating various composition of plasticizer namely ethylene carbonate (EC) with biopolymer–salt complexes carboxymethyl cellulose (CMC)–NH4Br.